Effect of partially replacing corn with sugar cane molasses on blood parameters and composition of the M. longissimus thoracis of growing pigs - Vanessa Peripolli; Gabriela Caillouel; Fernanda Ascencio Pace; Julia Helena Montes; Maiko Giorgi Philippe; José Laerte Nörnberg; Juahil Martins de Oliveira Júnior; Ivan Bianchi; Elizabeth Schwegler; Fabiana Moreira (Ciência Animal Brasileira, 2023)
The effect of sugar cane molasses, as a partial replacement to corn in the diet, on blood parameters and composition of the M. longissimus thoracis (LT) in growing pigs was explored in this study. Twenty female pigs aged 63 days, and weighing 28.98 ± 3.56 kg, were randomly assigned to either the control or sugar cane molasses treatments. Molasses was included at the 3% level to partially replace corn in their diet. Blood samples were collected at the beginning and end of the experiments. The animals were slaughtered at 110 days of age after 47 days in the experiment, weighing 67.9 ± 5.58 kg, and an LT muscle sample was extracted and evaluated. Each animal was considered an experimental unit. The treatment had no effect on the length and area of the LT muscle. Backfat thickness was reduced when using the sugar cane molasses treatment (5.80 mm) compared to the control treatment (8.90 mm) (P < 0.05). Higher enzyme gamma-glutamyl transferase (GGT) levels were observed in animals of the control treatment (67.10 IU/L) compared to animals treated with the sugar cane molasses treatment (49.90 IU/L) (P < 0.05). Moreover, the proximal composition, fatty acid profile, and quality were not influenced by treatment. Sugar cane molasses, used as an energy source to partially replace corn in the diet of growing pigs at a level of 3%, reduced the backfat thickness of the pig carcass and improved the serum concentration of the enzyme gamma-glutamyl transferase in pigs. Key words: eye muscle area; fatty acids; meat; pig; subcutaneous fat thickness